MODELAGEM NO ENSINO DE MATEMÁTICA: UM ESTUDO DE CASO COM ESTUDANTES CEGOS - Oliveira, Daiana de (2016)
The Basic Education receives students with special educational needs without being prepared for that. In this research we decided to work mathematics with blind students. Among the various math teaching methodologies we chose for Mathematical Modelling, in the perspective of Burak (1987, 1992, 1998). This choice was due to the understanding that Modeling is more attractive and significant, therefore, the process of teaching and learning for visually impaired students need to be dynamic. The question is: What shows modeling in mathematics education as a teaching methodology, from the development of proposed activities for students of Basic Education with visual impairment? The overall objective of this research was to know and investigate the methodological potential of mathematical modeling for the teaching of mathematics for elementary school students with visual impairments. Specifically, we propose to develop and discuss adapted activities, mediated by Mathematical Modeling for the blind students. Also, we intend to evaluate the potential of the teaching material used to give concrete support in the process of teaching and learning with students with visual impairments. Two students both 13 years old, attending the 9th grade of elementary school in regular schools, participated in this qualitative research, setting up a case study. The activities took place in APADEVI in different times of school classes, with an approximate duration of two months. The activities were carried out based on themes chosen by the students. The result of the developed activities indicates that: Mathematical modeling has the potential to constitute a methodology for the teaching of Mathematics for students with visual impairment, it favors a distinct dynamics of the usual classes, as well as allows the participation and dialogue between researcher and participants, and also enables the educational value of discussions of activities. Another observed result is a break with the linear and disciplinary vision of the curriculum. The educational object is constituted by a video and a guide offering subsidy to Math teachers of Basic Education, as a contribution to the Math teaching with blind students.